2015
DOI: 10.11604/pamj.2015.22.206.6066
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sex hormone levels, bone mineral density and bone turnover markers in healthy moroccan men: a cross-sectional study

Abstract: Introduction Gonadal steroid hormones play a crucial role during skeletal growth and maturation in both men and women. The aim of this study is to evaluate the relationship of sex hormone levels, bone mineral density and biochemical markers of bone turnover in healthy Moroccan men. Methods 142 Moroccan men who had no previous diagnosis of osteoporosis were enrolled prospectively in this cross-sectional study between December 2009 and August 2010. Also, subjects were exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There are also other examples of the involvement of aromatase in bone metabolism. The correlation between Estradiol and bone remodelling biomarkers has been proposed by a study where elderly men treated with an aromatase inhibitor displayed a significant increase in bone resorption as well as decreased bone formation biomarkers; once again suggesting that aromatase in combination with steroid precursors is relevant to bone health, especially in aged individuals [6].…”
Section: The Importance Of Aromatase In Hormonal Regulationmentioning
confidence: 90%
See 1 more Smart Citation
“…There are also other examples of the involvement of aromatase in bone metabolism. The correlation between Estradiol and bone remodelling biomarkers has been proposed by a study where elderly men treated with an aromatase inhibitor displayed a significant increase in bone resorption as well as decreased bone formation biomarkers; once again suggesting that aromatase in combination with steroid precursors is relevant to bone health, especially in aged individuals [6].…”
Section: The Importance Of Aromatase In Hormonal Regulationmentioning
confidence: 90%
“…The pathological changes involved in the progression of OA are caused by biomechanical forces as well as multiple autocrine, paracrine and endocrine cellular events which all contribute to perturbations of tissue homeostasis within the affected joint [4], [5]. Gonadal steroid hormones, such as Estrogen (E) and Testosterone (T), for example, are molecules that are biosynthesized in the body and play a key role in sexual development and reproduction, which includes regulating the vital process of skeletal growth and maturation, among other natural developmental processes in both men and women [6]. Sex hormones control the development of cartilage and bone as well as homeostasis according to sex.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental exposure: The relationship between smoking exposure and OP remains controversial; smoking was not associated with OP [28,49] while others considered cigarette smoking as a predictor for OP [43,56,73]. Among battery manufacturing workers, significant elevated levels of lead concentration were accompanied with OP when compared to healthy control.…”
Section: Menopause and Paritymentioning
confidence: 99%
“…Comparison between postmenopausal women according to their BMI showed that obese women had a higher BMD and lower prevalence of vertebral fractures [33,75]. Physical inactivity and low BMI are major risk factors of low BMD in both women and men [13,43,56,57,65,76].…”
Section: Body Mass Index (Bmi) and Physical Activitymentioning
confidence: 99%
“…A recent study observed novel metabolic profiling in postmenopausal women with a low BMD (16). Another prospective study suggested that intact parathyroid hormone and alkaline phosphatase levels were the most important independent factors associated with low BMD of the hip (17). To the best of our knowledge, no largescale study has been conducted to evaluate the relationship between global blood metabolites and osteoporosis.…”
mentioning
confidence: 99%